WORLD EXPERIENCE IN OVERCOMING FOREIGN INVESTMENT ATTRACTION AND FACTORS AFFECTING FOREIGN INVESTMENT ATTRACTION (American Journal of Business Management, Economics and Banking, 2025)
The dynamics of indicators determining the role of investment in the development of the economy is analyzed. Sources of financing investments directed at fixed capital have been considered. The factors influencing the attraction of foreign investment and world experience in eliminating them are also studied.